Liver Fat Content and Body Fat Distribution in Youths with Excess Adiposity (2018)
This study had two main objectives: To examine the association between body fat distribution and non-alcoholic fatty liver disease (NAFLD) and liver fat content, and to determine whether the relationship between NAFLD and regional body fat distribution, with respect to liver fat content in youths with excess adiposity, is independent of cardiorespiratory fitness (CRF) and a healthy diet. Liver fat content (controlled attenuation parameter (CAP)), body fat distribution (body mass index (BMI) z-score, waist circumference, waist-to-height ratio, fat mass/height, body fat percentage, total fat mass, android-to-gynoid fat mass ratio, visceral adipose tissue (VAT), and lean mass index, determined by dual-energy X-ray absorptiometry (DXA)), CRF (20-m shuttle-run test), and healthy diet (adherence to the Mediterranean diet by KIDMED questionnaire) were measured in 126 adolescents (66% girls) aged between 11 and 17 years. Participants were assigned to two groups according to the presence or absence of hepatic steatosis (CAP values >225 dB/m or <225 dB/m of liver fat, respectively). Considering the similar total fat values for the two groups (>30% by DXA), youths with NAFLD had higher fat distribution parameters than those without NAFLD, regardless of sex, age, puberty stage, lean mass index, CRF, and healthy diet (p < 0.01). In the non-NAFLD group, the association between hepatic fat and fat distribution parameters presented a similar pattern, although the association was statistically insignificant after adjusting for a potential confounding variable (ps > 0.05), except for the case of VAT. Body fat distribution parameters were higher in youths with NAFLD compared to those without NAFLD. Additionally, body fat distribution showed a significant association with liver fat content as assessed by CAP in youths with NAFLD independent of CRF and adherence to the Mediterranean diet, supporting the notion that upper body fat distribution might play a pivotal role in the development of NAFLD in adolescents. These results may have implications for the clinical management of youths with excess adiposity given the high prevalence of NAFLD in children and young adults.